Trends in vaccine investment in middle income countries. Issue 10 (3rd October 2019) - Onishchenko, K.; Hill, S.; Wasserman, M.; Jones, C.; Moffatt, M.; Ruff, L.; Pugh, S. J.
ABSTRACT: Although a proven and effective preventive health measure, childhood immunization programs remain vulnerable to budgetary pressures. Sustainable financing of immunization programs is an important issue that presents a challenge for middle-income countries (MIC) in particular, in part due to technological advances meaning more vaccines are available. This study aimed to analyse trends in immunization program investment across 15 MIC selected based on availability of data, income level classification, and regional representativeness. We assessed investment trends in relation to vaccine coverage, vaccine access, and broader health indicators. Immunization and expenditure data were obtained from the World Health Organisation (WHO) database and the WHO UNICEF Joint Reporting Form and WHO Vaccine Product, Price and Procurement from 2006–2016. We calculated a weighted average index of vaccine commitment (WAIVC) based on vaccine coverage, vaccine scope, and weighted by vaccine innovation measured by approximating vaccine expenditure. Correlation analyses were conducted between immunization expenditure per-capita and each WAIVC, infant mortality and life expectancy. Correlation analyses at a global and individual country level indicate an improvement in immunization access, vaccination commitment measured by WAIVC, and scope of available vaccines in countries with sustained increases in vaccination funding. Increases in national immunization expenditure were correlated with reduced infant mortality and increased life expectancy. Vaccine expenditure comprises a small proportion (less than 2%) of total healthcare spending and has not uniformly increased in accordance with the scope of available vaccines. The present analysis supports the premise that countries with consistent increases in vaccine expenditure have increased vaccine coverage and commitment measured by WAIVC and improved broader health outcomes, indicating the value of sustained investment in vaccination for improved population health. The benefits of vaccine expenditure in this holistic fashion are critical to inform policy decisions on national budget allocation for vaccine funding.